2007
DOI: 10.1530/rep-07-0022
|View full text |Cite
|
Sign up to set email alerts
|

AKR1B7 (mouse vas deferens protein) is dispensable for mouse development and reproductive success

Abstract: AKR1B7 (aldo-keto reductase family 1, member 7; also known as mouse vas deferens protein) is a member of the AKR superfamily, and has been suggested to play a role in detoxifying processes on account of its preferred substrates, 4-hydroxynonenal and isocaproaldehyde. High levels of protein expression were found in the vas deferens and the adrenal gland, where sustained expression is dependent on androgen or ACTH respectively. Recently, a remarkable induction of AKR1B7 expression has been reported in the ovary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 42 publications
5
13
0
Order By: Relevance
“…Interestingly, hepatic expression of Akr1b7 has no effect on MDA levels in the liver or plasma, thus raising a question regarding whether Akr1b7 regulates lipid peroxidation in vivo. The fi nding that Akr1b7 has no effect on hepatic MDA levels is consistent with the data from Akr1b7 Ϫ / Ϫ mice, in which no obvious changes in morphology or defects in reproduction have been observed ( 33 ). Despite the unchanged MDA levels, hepatic overexpression of Akr1b7 has pronounced effects on regulating lipid and glucose metabolism.…”
Section: Hepatic Expression Of Akr1b7 Ameliorates Hepatic Lipid Accumsupporting
confidence: 88%
“…Interestingly, hepatic expression of Akr1b7 has no effect on MDA levels in the liver or plasma, thus raising a question regarding whether Akr1b7 regulates lipid peroxidation in vivo. The fi nding that Akr1b7 has no effect on hepatic MDA levels is consistent with the data from Akr1b7 Ϫ / Ϫ mice, in which no obvious changes in morphology or defects in reproduction have been observed ( 33 ). Despite the unchanged MDA levels, hepatic overexpression of Akr1b7 has pronounced effects on regulating lipid and glucose metabolism.…”
Section: Hepatic Expression Of Akr1b7 Ameliorates Hepatic Lipid Accumsupporting
confidence: 88%
“…Although we have shown that activation of PXR was necessary and sufficient to decrease intestinal accumulation of the lipid peroxidation biomarker MDA, we cannot excluded the possibility that the MDA-lowering effect of PXR may have been mediated or contributed by PXR target genes other than Akr1b7. A future use of Ark1b7 null mice (Baumann et al, 2007) would further conclude that the PXR effect on the alleviation of lipid peroxidation is indeed mediated by this enzyme. Also interesting is that Akr1b7 has been suggested to affect lipid metabolism by inhibiting adipogenesis in some adipose tissues, the mechanism of which remains to be determined (Tirard et al, 2007).…”
Section: Downloaded Frommentioning
confidence: 97%
“…Among AKR isoforms, the mouse Akr1b7 is highly expressed in vas deferens and adrenal gland, in which its sustained expression is dependent on androgen and adrenocorticotropic hormone, respectively (Lau et al, 1995). It is interesting that Akr1b7 null mice were found to be viable and have no obvious defect in reproduction (Baumann et al, 2007). Besides the steroidogenic tissues, Akr1b7 is also expressed in mouse kidney, eye, intestine, and, at a lower level, in liver (Lau et al, 1995).…”
mentioning
confidence: 99%
“…In addition, the spermatozoa membrane has a higher content of polyunsaturated fatty acids, which through peroxidation generates 4-HNE, a toxic product that is inactivated by aldo-keto reductases (Kobayashi et al 2002). Another hint on the possible function of ARY is that the aldo-keto reductase ARK1B7 is expressed at very high levels in the male reproductive tract in the mouse (Baumann et al 2007). Knockout of ARK1B7 seems to cause partial sperm impairment, although the animals have normal fertility (Tables 3 and 4 in Baumann et al 2007).…”
mentioning
confidence: 99%
“…Another hint on the possible function of ARY is that the aldo-keto reductase ARK1B7 is expressed at very high levels in the male reproductive tract in the mouse (Baumann et al 2007). Knockout of ARK1B7 seems to cause partial sperm impairment, although the animals have normal fertility (Tables 3 and 4 in Baumann et al 2007). Hence, it seems that ARY is another case of a male-specific gene recruited by the Drosophila Y.…”
mentioning
confidence: 99%